2021
DOI: 10.1016/j.xjidi.2021.100047
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Phenotype-Based Clustering of Clinicopathologic Features in Cutaneous Melanoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Interestingly, through machine learning, five clusters of melanomas were identified which occupied two distinct clinicopathologic subspaces: a lower‐grade partition associated with acquired melanocytic nevi (NAM) and a higher‐grade partition lacking precursor lesions ( de novo melanoma). The authors' model confirmed differences between NAM and de novo melanoma previously reported in observational studies, showing that de novo melanoma was more mitogenic, ulcerative and thicker than NAM 39 …”
Section: Epidemiological Clinical and Histologic Characteristics Of N...supporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, through machine learning, five clusters of melanomas were identified which occupied two distinct clinicopathologic subspaces: a lower‐grade partition associated with acquired melanocytic nevi (NAM) and a higher‐grade partition lacking precursor lesions ( de novo melanoma). The authors' model confirmed differences between NAM and de novo melanoma previously reported in observational studies, showing that de novo melanoma was more mitogenic, ulcerative and thicker than NAM 39 …”
Section: Epidemiological Clinical and Histologic Characteristics Of N...supporting
confidence: 86%
“…The authors' model confirmed differences between NAM and de novo melanoma previously reported in observational studies, showing that de novo melanoma was more mitogenic, ulcerative and thicker than NAM. 39…”
Section: Introductionmentioning
confidence: 99%